Dietary SCFAs, IL-22, and GFAP: The Three Musketeers in the Gut–Neuro–Immune Network in Type 1 Diabetes - Jayasimhan, Abhirup; Mariño, Eliana (Frontiers in Immunology, 2019)
Microbial metabolites have a profound effect on the development of type 1 diabetes (T1D). The crosstalk between the gut microbiota the nervous and immune system is necessary to establish and maintain immune and gut tolerance. As quoted by Hippocrates, “All disease begins in the gut.” Although this has been recognized for 2000 years, the connection between the gut and autoimmune T1D is not yet well understood. Here we outline new advances supported by our research and others that have contributed to elucidate the impact of microbial metabolites on the physiology of the pancreas and the gut through their remarkable effect on the immune and nervous system. Amongst many of the mechanisms involved in the gut-beta cell-immune crosstalk, Glial Fibrillary Acidic Protein (GFAP)- expressing cells are critical players in the development of invasive insulitis. Besides, this review reveals a novel mechanism for microbial metabolites by stimulating IL-22, an essential cytokine for gut homeostasis and beta cell survival. The close connections between the gut and the pancreas are highlighted through our review as microbial metabolites recirculate through the whole body and intimately react with the nervous system, which controls essential disorders associated with diabetes. As such, we discuss the mechanisms of action of microbial metabolites or short chain fatty acids (SCFAs) on immune cells, beta cells, gut epithelial cells, neurons, and glial cells via metabolite sensing receptors or through epigenetic effects. The fine-tuned gut-neuro-immune network may be profoundly affected by SCFAs deficiency related to dysbiosis and diet alterations at very early stages of the initiation of the disease. Thus, dampening the initial​ immune response or preventing the perpetuation of the immune response by maintaining the integrity of the gut is among alternative approaches to prevent T1D.